Effect of carbopol gel in stable liposomes and their enhanced antipyretic effect - Suriaprabha, Kannaiyan; Pichandy, Muthuprasanna; Vanchasatya, Vardhareddy (Asian Journal of Pharmaceutics (AJP), 2014)
The modified liposomes formulated with carbopol (CP) polymer might be promising for their enhanced stability and antipyretic action. The formulation of liposomes was performed to obtain the minimum concentration of the gel to enhance the stability of the vesicles and to prove the efficacy of the liposome in promoting the antipyretic activity of the drug. The liposome formulation was found to be more effective than the marketed antipyretic drug. A 1.5% CP could be considered as the minimum concentration for the gel to maintain the liposome stable than a 0.5% CP polymer.The surfactant, Polysorbate 80, helped to form spherical vesicles and CP polymer-1.5% w/w was found to show enhanced stability of the formulation.The concentration of 1.5% CP seemed to give the necessary mechanical strength to the liposomal formulation. A drug delivery system by the modified liposomes may be considered for further investigation for validating and standardizing this formulation for the controlled drug release system toward enhancing maximum therapeutic efficacy.